Safety of patwardhan technique in deeply engaged head - Bansiwal, Reeta; Anand, HP; Jindal, Meera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Deeply engaged head in second stage caesarean section is not new, every obstetrician must have faced it and its associated problems many times in their career. Caesarean sections done at full cervical dilatation with impacted foetal heads are technically difficult as the lower segment is thinned out and oedematous and hence associated with an increased incidence of maternal and foetal morbidities. The objective of this study was to compare patwardhan technique with Push and pull technique of delivering deeply impacted head and to assess the safety of patwardhan technique by correlating them with maternal and fetal outcome. Methods: It is a retrospective study including all caesarean sections done in second stage at Tertiary care centre, New Delhi, India in the years from 2011 to 2013. Patients were divided into two groups: group -1 where baby delivered by Patwardhan technique and group 2 where baby delivered by push or pull technique. Both groups were compared in terms of maternal outcomes as uterine incision extensions, PPH, blood transfusions and neonatal outcomes in terms of their weight, APGAR and NICU stay. Results: There were total 135 patients who underwent caesarean section for obstructed labour during 2011-2013. Out of 135, 71 babies were delivered by push and pull method and 64 babies got delivered by Patwardhan technique. There was significant less uterine incision extensions in patwardhan group as compared to push and pull technique (3.1%, 23.9%: p=0.01). The traumatic PPH and blood transfusion was also significantly high in push and pull method as compared to patwardhan technique (1.5%, 22.5%: p=0.01). Baby outcome was almost similar in both the groups. Conclusions: The patwardhan technique needs expertise but is safe and has minimal complications if anticipated and done skill fully. It is easy to learn and needs to be more widely publicized and utilized.